Immanuel Kant’s Aesthetics: Beginnings and Ends - Fenner, David (Con-Textos Kantianos. International Journal of Philosophy, 2020)
Immanuel Kant and his work occupied a space at the crossroads of several important movements in philosophy. In this essay, I look at two important crossroads in aesthetics. First, the subjective turn in aesthetics, when the focus on aesthetic objects (and events) was rebalanced with the focus on the subject’s experience of such objects, the weight shifting from the objective to the subjective. Second, after many years and many theories advancing the view that universality of judgment could be achieved, at least in part, through adoption of the appropriate perspective – or attitude – when considering a particular aesthetic object, Kant offers us perhaps the most sophisticated view of disinterestedness of any, and as he does so he solidifies that tradition, bringing it to its culmination, and ushers in the beginning of its end.